1999
DOI: 10.1159/000027455
|View full text |Cite
|
Sign up to set email alerts
|

Visual Outcome after Treatment with Low-Dose Recombinant Tissue Plasminogen Activator or Hemodilution in Ischemic Central Retinal Vein Occlusion

Abstract: The ischemic type of central retinal vein occlusion (CRVO) is associated with a poor visual and ocular prognosis. Although several reports have indicated that hemodilution or thrombolytic therapy may be of benefit, there is still no consensus among ophthalmologists about the management of this disorder. In our study, we retrospectively evaluated the visual outcome after medical treatment in 58 patients with ischemic CRVO and severe visual loss (≤20/50). We separately investigated three different groups, depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 26 publications
(41 reference statements)
1
9
0
Order By: Relevance
“…Most of these studies did not take into account the presence of cardiovascular risk factors or patient age by the time of the RAO. However, previous investigations on the role of thrombophilia in retinal vascular occlusive diseases had indicated that thrombophilia screening in affected individuals should be selective [14,15,16,17,28,29,30,31,32,33,34]. In the present study, we investigated a highly preselected subgroup of younger patients with RAO who had undergone a comprehensive routine screening for thrombophilic disorders that have been associated with arterial occlusive diseases, including protein C and protein S, antithrombin III, resistance to APC, factor II gene polymorphisms, anticardiolipin antibodies, factor VIII:C, PAI-1 activity, homocysteine and Lp(a) levels, and factor XII.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies did not take into account the presence of cardiovascular risk factors or patient age by the time of the RAO. However, previous investigations on the role of thrombophilia in retinal vascular occlusive diseases had indicated that thrombophilia screening in affected individuals should be selective [14,15,16,17,28,29,30,31,32,33,34]. In the present study, we investigated a highly preselected subgroup of younger patients with RAO who had undergone a comprehensive routine screening for thrombophilic disorders that have been associated with arterial occlusive diseases, including protein C and protein S, antithrombin III, resistance to APC, factor II gene polymorphisms, anticardiolipin antibodies, factor VIII:C, PAI-1 activity, homocysteine and Lp(a) levels, and factor XII.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodilution is expected to prevent the slowdown of blood circulation and its complications by dramatically lowering blood viscosity. Some randomized studies have been published on the topic and concluded on a statistically significant difference between treated and nontreated patients [61,79,80,81,82]. Nevertheless, these monocenter studies were conducted in the 1980s and 1990s, and they used different treatment protocols.…”
Section: Managementmentioning
confidence: 99%
“…Recombinant tissue plasminogen activator (rtPA) is a synthetic fibrinolytic agent that converts plasminogen to plasmin and destabilizes intravascular thrombi. rtPA, as therapy against CRVO, has been administered by several routes: systemic [13,14], intravitreal [15,16,17], and by endovascular cannulation of retinal vessels either through a neuroradiological or a vitreoretinal approach, and delivery of minute quantities of rtPA directly to the occluded vessels to release the suspected thrombus [18,20,21]. …”
Section: Central Retinal Vein Occlusionmentioning
confidence: 99%